1977
DOI: 10.2136/sssaj1977.03615995004100040013x
|View full text |Cite
|
Sign up to set email alerts
|

Basaluminite and Alunite: A Possible Cause of Sulfate Retention by Acid Soils

Abstract: Pure‐solution and soil‐solution experiments were conducted in which the solubility products of synthetic basaluminite and alunite in pure solutions were compared with the ion‐activity products of Al4(OH)10SO4 and KAl3(OH)6(SO4)2 in soil solutions of sulfate‐treated soil. Solution experiments were conducted in which 0.05M Al2(SO4)3 was titrated with NaOH, KOH, or Ca(OH)2 to an OH/AI mole ratio of 2.0. The initial precipitate was amorphous, with the chemical composition of basaluminite, Al4(OH)10SO4·5H2O. Aging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
10

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(76 citation statements)
references
References 0 publications
2
63
1
10
Order By: Relevance
“…A redução nos teores de Al 3+ tóxico, em decorrência da aplicação de gesso, ocorre pela precipitação de Al e formação de minerais (Adams & Rawayfih 1977), ou, também, pela lixiviação de Al com o gesso, na forma de pares iônicos ou complexos AlSO 4 + (Pavan et al 1984).…”
Section: +unclassified
“…A redução nos teores de Al 3+ tóxico, em decorrência da aplicação de gesso, ocorre pela precipitação de Al e formação de minerais (Adams & Rawayfih 1977), ou, também, pela lixiviação de Al com o gesso, na forma de pares iônicos ou complexos AlSO 4 + (Pavan et al 1984).…”
Section: +unclassified
“…Barite (BaSOJ has been found in a variety of soils (Crum and Franzmeier, 1980;Lynn et al, 1971) and celestite (SrSO^) was identified in some arid soils (Abtahi et al, 1980 (Adams and Rawajfih, 1977;Carson and Dixon, 1983;Clark et al, 1961;Fleming and Alexander, 1961;Hue et al, 1985;Khanna et al, 1987;Nordstrom, 1982;Tsai and Hsu, 1984;Wagner et al, 1982;Wolt, 1981). In addition, other Na-rich Fe or A1 sulfates such as natrojarosite [NaFe3(0H)g(804)2] (Pawluk and Dudas, 1978) and natroalunite [NaAl3(0H)g(804)2] (Chitale and Guven, 1987) may form in some soils.…”
Section: Inorganic Forms Of Sulfurmentioning
confidence: 99%
“…He also hypothesized that jurbanite may form from gibbsite and is responsible for activity in acid forest soils. Earlier studies by Adams and Rawajfih (1977) showed that Al-hydroxyl surface of the solid phase could be an important mechanism controlling 80/' and Al®" activities in soils. In their experiments, they showed that the formation of sparingly soluble alunite and basalunite from, or onto the surface of gibbsite, was thermodynamically favorable.…”
mentioning
confidence: 99%
“…Numa superfície positiva, o SO 4 2-é adsorvido como bidentado, formando estrutura anelar de seis membros que, segundo Hingston et al (1974), favorece a irreversibilidade, ou seja, formas não lábeis. Adams & Rawajfih (1977) sugeriram a precipitação e dissolução da basalunita e alunita e de sais análogos de Fe como mecanismos plausíveis para os fenômenos de sorção de SO 4 2-em solos ácidos.…”
Section: Introductionunclassified